(untitled) (Research, Society and Development, 2024)
The aim of this clinical protocol is to describe the methodology for the evaluation of the clinical performance of Hall Technique (HT) in comparison with glass ionomer cement (GIC) restorations in first permanent molars (FPM) severely affected by molar incisor hypomineralization (MIH). This protocol is related to a two-arm, parallel group, controlled and randomized superiority trial. It will be included 92 participants, 6 to 12 years-old, presenting at least one FPM with post-eruptive enamel breakdown and/or atypical caries and/or unsatisfactory atypical restoration involving cusp and extending to at least two tooth surfaces. Two trained and calibrated dentists will select the participants and assess the outcomes. Eight experienced clinicians who work as dentists at the public oral health system will be trained to perform the interventions. The participants will be randomized into the test (HT) or the control group (GIC). The outcomes will be assessed every 6 months up to 3 years. The primary outcome is the survival rate of the restorations. Secondary outcomes include satisfaction of the participants, parents, and dentists; impact on oral heath related quality of life; self-reported discomfort during treatment; signs/symptoms of temporomandibular joint dysfunction; and cost-effectiveness. Kaplan-Meier and Cox regression analysis will be used to analyze the primary outcome. Mann-Whitney or t-test will be used to compare the secondary outcomes between groups. We expect to provide scientific evidence about the treatment approach that maximizes success rates and minimizes retreatments in severe HMI.